Finite element simulation on thermal fatigue of a turbine blade with thermal barrier coatings - Yang, Li; Liu, Qixing; Zhou, Yi-Chun; Mao, Weiguo; Lu, Chunsheng (Zhongguo Kexueyuan Jinshu Yanjiusuo, 2014)
In this paper, a finite element model was developed for a turbine blade with thermal barrier coatings to investigate its failure behavior under cyclic thermal loading. Based on temperature and stress fields obtained from finite element simulations, dangerous regions in ceramic coating were determined in terms of the maximum principal stress criterion. The results show that damage preferentially occurs in the chamfer and rabbet of a turbine blade with thermal barrier coatings and its thermal fatigue life decreases with the increase of thermal stress induced by high service temperature.